Effectiveness of State Trading Enterprises in Achieving Food Security: Case Studies from Bernas in Malaysia and Bulog in Indonesia - Fatimah Mohamed Arshad; Bustanul Arifin; Yeong Sheng Tey (Center for Indonesian Policy Studies (CIPS), 2019)
Rice is such an important commodity for the food security of countries such as Indonesia and Malaysia. State Trading Enterprises (STEs) have often taken the lead on ensuring access to this key commodity. However, these entities are often criticised for creating market distortions through their monopolistic nature. Center for Indonesian Policy Studies (CIPS), in collaboration with Malaysian think-tank, IDEAS, has published a policy paper that outlines the impacts and contributions of STEs through Bulog in Indonesia, and Bernas in Malaysia, on Asia's essential rice commodity.
Keywords: 330